If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = 3h + -4 Reorder the terms: 14 = -4 + 3h Solving 14 = -4 + 3h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-3h' to each side of the equation. 14 + -3h = -4 + 3h + -3h Combine like terms: 3h + -3h = 0 14 + -3h = -4 + 0 14 + -3h = -4 Add '-14' to each side of the equation. 14 + -14 + -3h = -4 + -14 Combine like terms: 14 + -14 = 0 0 + -3h = -4 + -14 -3h = -4 + -14 Combine like terms: -4 + -14 = -18 -3h = -18 Divide each side by '-3'. h = 6 Simplifying h = 6
| x^4-6x^3+8x^2+6x=0 | | 5x-10-3=17 | | -9(1-2a)=18 | | (3p-1)(3p+1)= | | 0.15x-2.1=0.3(x-5) | | 4a-7b=0 | | x^2=-x^2+8 | | 14x-10=17x-19 | | 4/u=8 | | X^22+14x+49=0 | | x+133=32 | | 2(g-f)=10 | | 6t+11=2t-27 | | 8x^2+10xy+3y^2=0 | | 2(g-h)=10 | | 5z-21=2z | | 3a+21=5a-7 | | 5*3.6= | | x^4+8x^2+15x=0 | | -3+z=7 | | 4+10x=5+x | | n+3=72 | | k+(-1)=9 | | c+4=3c | | 6+e*f=30 | | 15y+12=19y | | 15-4x=17-4x | | 4x3/2-5=103 | | 5x+8-x=20+4x | | 0.8x-0.7=8.1 | | 7b-7=6b | | f+34=47 |